The gangster - Cussler, Clive; Scott, Justin (Cussler, Clive. Isaac Bell novels., 2016)
"It is 1906, and in New York City, the Italian crime group known as the Black Hand is on a spree: kidnapping, extortion, arson. Detective Isaac Bell of the Van Dorn Agency is hired to form a special 'Black Hand Squad,' but the gangsters appear to be everywhere--so much so that Bell begins to wonder if there are imitators, criminals using the name for the terror effect. And then the murders begin, each one of a man more powerful than the last, and as Bell discovers, to his dismay, the ultimate target may be the most powerful man of all"--